The Cancellation of The Weddings for Pre-Marriage Pregnancy Women: An Evaluation of Decision 24/Pdt.G/2020/Ms. Ban - Zainuddin, Muslim (El-Usrah: Jurnal Hukum Keluarga, 2023)
Marriage annulment is not limited to cases of polygamy without permission, remarriage during the 'iddah period, marriages without a guardian, or coerced marriages could also be annulled. In Decision Number 24/Pdt.G/2020/Ms. Ban, the court annulled the marriage of a minor who were pregnant pre-marriage. This is a normative legal research focusing on statutory regulations and legal concepts to address this issue. Legal sources used include primary, secondary, and tertiary sources, and a qualitative approach was used to analyze the data. The findings of this study indicate that the procedure for requesting an annulment of a marriage involves submitting a request to the Syar'iyah Court along with supporting evidence in the form of documents and the testimony of witnesses who witnessed the marriage event. The panel of judges declared the marriage between the petitioner and the respondent null and void at the conclusion of the trial, rendering the marriage certificate null and void. In addition, the judicial tribunal requested that the Religious Affairs Office (KUA) remove the marriage record from the register book. The reason for annulling a marriage is that it was performed by the sibling of the applicant’s father. However, the applicant’s father did not have the authority to be a marriage guardian because the applicant was an illegitimate child; therefore, he had only a relationship with his mother and her family. Legally, the annulment of the marriage is justified because the marriage between the petitioner and the respondent does not comply with the statutory requirements and conditions. One of the unfulfilled pillars is the lack of a guardian with the authority to solemnize the marriage. Supposedly, the guardian of children conceived outside of marriage should be a judge.